Geoelectrical Investigation of the Groundwater Potential at Laniba, Akinyele Local Government area of Ibadan, Oyo State - Joshua, Emmanuel Oluwagbemi; Aboje, Benjamin Inalegwu; Ariyibi, Emmanuel A.; Adewoyin, Olusegun Oladotun (Journal of Informatics and Mathematical Sciences, 2017)
Vertical Electrical Sounding (VES) was carried out at Laniba area, Ibadan, Oyo state, Nigeria in order to study the subsurface geologic layer with view of determining the depth to the bedrock and thickness of the geologic layers. The ABEM terrameter (SAS 300B) was used for data acquisition in twenty two (22) VES stations. The field data obtained has been analyzed using computer software (IPI2win) which gives an automatic interpretation of the apparent resistivity. The VES results revealed heterogeneous nature of the subsurface geological sequence.\ The geologic sequence beneath the study area is composed of hard pan topsoil (clayed and sandy lateritic weathered layer), partly weathered or fractured basement and fresh basement. The resistivity value for the topsoil layer varies from 36.1 to 185.0 \(Ω\)m with thickness ranging from 0.1 m to 1.4 m, the weathered basement has resistivity value ranging from 98.0 to 1098.8 \(Ω\)m and thickness of between 0.1 m to 1.4 m, the fractured layer has resistivity ranging from 51.5 to 1178.0 \(Ω\)m, the fresh basement (bedrock) has resistivity value ranging from 39.1 to 1010.2 \(Ω\)m with infinite depth. However, the depth from the earth surface to the bedrock surface varies from 3.1 to 35.5 m.